2007
DOI: 10.1590/s0004-282x2007000500018
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal nerve palsy due to compartment syndrome after facial plastic surgery

Abstract: -A 25-year-old white man, right after bilateral rhytidoplasty, presented with agitation, necessiting use of haloperidol. Some hours after, he developed severe pain in his legs and a diagnosis of neuroleptic malignant syndrome (NMS) was considered. Even with treatment for NMS he still complained of pain. A diagnosis of lower limb compartment syndrome (CS) was done only 12 hours after the initial event, being submitted to fasciotomy in both legs, disclosing very pale muscles, due to previous ischemia. This syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Segundo Rosa et al (2005);Godeiro Júnior et al (2007) devido esta liberação CK na corrente sanguínea, é possível usá-la para o diagnóstico da SC. No presente relato, a dosagem sérica de CK não foi utilizada, uma vez que os sinais da SC foram identificados já em estágio avançado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Segundo Rosa et al (2005);Godeiro Júnior et al (2007) devido esta liberação CK na corrente sanguínea, é possível usá-la para o diagnóstico da SC. No presente relato, a dosagem sérica de CK não foi utilizada, uma vez que os sinais da SC foram identificados já em estágio avançado.…”
Section: Discussionunclassified
“…Mas adjunto aos sinais clínicos deve-se utilizar métodos de confirmação como a mensuração da pressão intracompartimental pela técnica de Whitesides (Whitesides Junior et al, 1975). Além da dosagem sérica de creatina quinase (CK) para identificação precoce da rabdomiólise (Vanholder et al, 2000;Rosa et al, 2005;Godeiro Júnior et al, 2007). Na maioria das vezes, os sinais da SC causam dor e edema, tornando difícil o diagnóstico, pois existe uma série de patologias que podem simular a SC como: celulite, osteomielite, fratura por estresse, tenossinovite e trombose venosa profunda (Uliasz et al, 2003).…”
Section: Introductionunclassified
“…Among the mechanisms of earthquake‐related PNI examined in this study, compartment syndrome was found in 15 (39.5%) of the 38 patients. Due to the increased intracompartmental pressure resulting from compartment syndrome, the muscles and peripheral nerves in the trapped extremities can be affected by ischemia 17–19. Although EMG is an important diagnostic tool for obtaining data regarding the severity and extent of nerve injury, it may be difficult to perform when a patient has injuries to more than one extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Associated conditions were reported in 29 cases, two had no other associated conditions [ 13 , 22 ], and two did not have information available [ 16 , 23 ]. The most frequently occurring complications or associated conditions were renal impairment (14 patients), rhabdomyolysis (12 patients), and infection (11 patients) (Table 2 ).…”
Section: Reviewmentioning
confidence: 99%